Effect of different building façade systems on thermal comfort and urban heat island phenomenon: An experimental analysis. (1st June 2022) - Wonorahardjo, Surjamanto; Sutjahja, Inge Magdalena; Mardiyati, Y.; Andoni, Heri; Achsani, Rizky Amalia; Steven, S.; Thomas, Dixon; Tunçbilek, Ekrem; Arıcı, Müslüm; Rahmah, Nadiya; Tedja, Suwardi
Abstract: This study experimentally investigates the effect of different façades systems on thermal comfort and urban heat island (UHI) phenomenon by using experimental tools. Outdoor field measurements are conducted for brick, concrete, low-E glass, aluminium composite panel (ACP), and clear glass to observe the effect of morning solar exposure on the east-west façade surface temperatures. Two different types of insulation materials, namely newspaper and corn husk mat, are also manufactured and considered. Then, laboratory experiments are performed with 1 m × 1 m panel under two 1000 W halogen lamps by measuring air, surface and material temperatures using a thermocouples data-logger with a recording interval of 5 min and IR thermovision for visual confirming. The lamps simulate solar exposure during morning (8.00 a.m.–12.00 p.m.). It is noted that the brick wall stores heat during solar exposure, and then emits that heat to indoor and outdoor environments. Additional ACP to the brick wall reduces indoor air temperature significantly whereas direct impact on the outdoor temperature should also be accounted to avoid UHI. Besides, insulation material is found to be only beneficial during heating period in terms of reducing the indoor air temperature, however it slightly incremented the outdoor air temperature. This study shows how different façade systems of buildings significantly affect both the indoor and outdoor environments. It is revealed that, in the design process, the indoor air temperature should be considered for thermal comfort while the outdoor air temperature should be considered for UHI phenomenon. Highlights: Effect of building façade to indoor and outdoor environment was investigated experimentally. Role of façade and cellulose-based insulating materials was identified. Outside insulation reduces/increases air temperature for the indoor/outdoor environments. Building envelope affects heat storage/release to indoor and outdoor environment.